The Effect Of Applying Group Guidance With A Storytelling Technique Approach To Improve Student Polite Behavior Of Student Grade V SD 3 Wates In The Academic Year 2021/2022 - Zulfatul Khafidah; Eko Nusantoro (ARKA INSTITUTE, 2022)
The purpose of this study was to obtain data showing the effect of group guidance using the storytelling technique on improving manners in fifth grade students of SD 3 Wates for the 2021–2022 academic year. This type of research is an experiment with a one group pre-test post-test research design. methods of data collection using interviews and questionnaires to improve manners The data analysis technique used is percentage descriptive analysis and the Wilcoxon test. The results of the study showed that there was a change in the level of politeness of students before and after participating in group guidance services using storytelling techniques. It can be seen that the results show an average increase of 15.2% from the initial results. Because the number of levels is the smallest, the value of Tcount is 0 and the value of Ttable is 8, also 0 < 8, then Ha is accepted and Ho is rejected. Asymp value. Its sig of 0.005 is less than 0.5. This means that group guidance services using storytelling techniques have a significant influence on improving the manners of fifth grade students at SDN 3 Wates, Kudus Regency.